Medial Frontal Cortex Activity and Loss-Related Responses to Errors - Taylor, Stephan F. (J Neurosci, 2006)
Making an error elicits activity from brain regions that monitor performance, especially the medial frontal cortex (MFC). However, uncertainty exists about whether the posterior or anterior/rostral MFC processes errors and to what degree affective responses to errors are mediated in the MFC, specifically the rostral anterior cingulate cortex (rACC). To test the hypothesis that rACC mediates a type of affective response, we conceptualized affect in response to an error as a reaction to loss and amplified this response with a monetary penalty. While subjects performed a cognitive interference task during functional magnetic resonance imaging, hemodynamic activity in the rACC was significantly greater when subjects lost money as a result of an error compared with errors that did not lead to monetary loss. A significant interaction between the incentive conditions and error events demonstrated that the effect was not merely attributable to working harder to win (or not lose) money, although an effect of motivation was noted in the mid-MFC. Activation foci also occurred in similar regions of the posterior MFC for error and interference processing, which were not modulated by the incentive conditions. However, at the level of the individual subject, substantial functional variability occurred along the MFC during error processing, including foci in the rostral/anterior extent of the MFC not appearing in the group analysis. The findings support the hypothesis that the rostral extent of the MFC (rACC) processes loss-related responses to errors, and individual differences may account for some of the reported variation of error-related foci in the MFC.